Microperforate hymen presenting as tubo-ovarian abscess in adulthood - Tan, GI; Balakrishnan SS,; Parampalam SD, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Microperforate hymen is a rare vaginal anomaly that is usually reported in childhood due to recurrent urogenital infections. Unlike imperforate hymen where the presenting complaints are classical due to complete vaginal obstruction, the less profound and varied presentation of microperforate hymen may go unnoticed. We report a case of a 39-year-old, with a background history of amenorrhea, who presented with acute abdomen suggestive of tubo-ovarian abscess, and was finally diagnosed to have microperforate hymen. She underwent hymenectomy to correct the anomaly. To our knowledge, this is the oldest age of presentation of a congenital form of microperforate hymen. A high index of suspicion and early detection of microperforate hymen and properly timed intervention is essential to prevent acute symptoms and long term detrimental sequalae to women’s reproductive and psychosexual health.